The Clinical Trade-off between Rapid Hemodynamic Stabilization and Respiratory Morbidity in Pediatric Dengue Shock Syndrome: A Meta-Analysis of Colloid versus Crystalloid Resuscitation - Ni Nyoman Putri Widyastiti; I Nyoman Putra Arcana (HM Publisher, 2026)
Background: Fluid resuscitation is the cornerstone therapy for pediatric Dengue Shock Syndrome (DSS), a condition defined by profound endothelial hyperpermeability. The choice between crystalloids and colloids presents a clinical paradox. Crystalloids are standard first-line therapies, whereas colloids offer rapid intravascular expansion for refractory shock. This study quantifies the trade-off between the rapid hemodynamic stabilization provided by colloids and the subsequent iatrogenic risk of respiratory morbidity in pediatric DSS. Methods: Following PRISMA guidelines, a systematic review and meta-analysis were conducted. We searched MEDLINE, Scopus, and Cochrane databases for original randomized controlled trials (RCTs) and cohort studies comparing crystalloid and colloid regimens in pediatric DSS. To address methodological heterogeneity, efficacy outcomes (time to hemodynamic stabilization) from RCTs and safety outcomes (respiratory morbidity) from observational cohorts were analyzed separately. Standardized mean differences (SMD) and odds ratios (OR) with 95% confidence intervals (CI) were calculated using random-effects models. Results: Seven studies encompassing 2,477 pediatric patients were included. Meta-analysis of RCTs demonstrated that colloid-containing regimens achieved significantly faster initial hemodynamic stabilization compared to crystalloid-only regimens (SMD -0.62, 95% CI -0.85 to -0.39). Conversely, meta-analysis of cohort data revealed that mixed or colloid-heavy regimens were associated with a markedly increased risk of respiratory morbidity and mechanical ventilation requirements (OR 2.45, 95% CI 1.68 to 3.57). Overall shock recovery was prolonged in mixed-fluid groups. Conclusion: A definitive clinical trade-off exists in pediatric DSS management. Colloids rapidly restore early hemodynamics but significantly increase late-stage respiratory morbidity and ventilation requirements. This supports a restrictive, crystalloid-first resuscitation strategy. Future randomized trials are urgently needed to specifically evaluate the safety of natural colloids, such as 5% albumin, versus synthetic starches and gelatins.